(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2017)
The insurance activity in the various countries of the world are important indicators of the strength of the country’s economy, he came to study the stages compensation insurance settlement against fire and the importance of investing time risk in achieving the payment of compensation speed, and the implications for the continuation of the insured to carry out insurance with the insurance company, whether working within the public sector or the private sector. Hence the research problem in how quickly insurance companies to pay compensation as soon as possible and the return of the insured to carry out its work and make up for what he died from loss. Intentional sample was selected from branches and divisions and Their assistants managers in the size of the surveyed companies (52) Branch Manager and department and their assistants representing the middle management of the two companies from the public and the private insurance sector in Baghdad. The most significant results that have been reached indicate a strong correlation strength statistically significant differences between time management variables separately and stages of the settlement of compensation, which confirms the presence of high impact to the variables of time management in stages compensation insurance settlement from the fire.